1992
DOI: 10.2337/diacare.15.11.1598
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Double-Blind Trial in Healing Chronic Diabetic Foot Ulcers: CT-102 activated platelet supernatant, topical versus placebo

Abstract: CT-102 significantly accelerated wound closure in diabetic leg ulcers when administered as part of a comprehensive program for the healing of chronic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
180
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(185 citation statements)
references
References 15 publications
1
180
0
4
Order By: Relevance
“…Platelets, platelet-rich plasma (PRP), platelet lysates, platelet-derived growth factor (PDGF), and supernatants from activated platelets all have well-known stimulatory effects on mesenchymal cells in vitro (4-10) and in vivo (11). The clinical potential of platelet constituents is interesting and several clinical trials and observations on wound healing and bone formation have been published (12)(13)(14)(15)(16)(17)(18). Previously, it has also been described that mineralization and bone repair is pH dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets, platelet-rich plasma (PRP), platelet lysates, platelet-derived growth factor (PDGF), and supernatants from activated platelets all have well-known stimulatory effects on mesenchymal cells in vitro (4-10) and in vivo (11). The clinical potential of platelet constituents is interesting and several clinical trials and observations on wound healing and bone formation have been published (12)(13)(14)(15)(16)(17)(18). Previously, it has also been described that mineralization and bone repair is pH dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of PRP have demonstrated antimicrobial activity against Escherichia coli, Staphylococcus aureus [31,32], including methicillin-resistant Staphylococcus aureus [31], Candida albicans [31] and Cryptococcus neoformans [33]. This suggests its role as antimicrobial and has the potential to eradicate the infective pathogens from the site and boost the healing process.…”
Section: Properties Of Platelet-rich Plasma Towards Wound Healing Andmentioning
confidence: 99%
“…A very small study (in which the definition of healing was not clear) reported an apparent benefit of the product in neuropathic ulcers [51]. A large cohort study of neuropathic ulcers reported significant benefit but was weakened by being a retrospective analysis of a database of the outcome of patients treated with different doses and for different periods with a platelet-derived product, and compared with those who did not receive it but were otherwise managed but in no specified way [52].…”
Section: Platelets and Platelet-derived Productsmentioning
confidence: 99%